2014 Malaysia flood: Impacts & factors contributing towards the restoration of damages - Sunitha V. Doraisamy, Sunitha V. Doraisamy; Zainal Abidin Akasah, Zainal Abidin Akasah (2015)
The 2014 flood that happened from December 2014 to January 2015 is considered to be the worst flood in a decade. There was an outpouring support from other international officials in terms of moral, physical and also donations. The impact of this flood left the nation with expensive damages and great devastation as well. This paper looks into the impact of the flood in terms of losses, damages and costs towards the nation. The impact is illustrated by obtaining data, statistics and also visuals of the recent flood. From this paper, a correlation between the restorations of abandoned projects in Malaysia with future restoration that is intended for the damages caused by this flood is also shown here, where these factors were developed through observation and measurements from literature reviews and other officials related to project restorations. An understandable and clear view has been established on this catastrophe. Here, some guidelines and factors has also been identified, hoping to contribute towards the restoration of this damages in Malaysia. The estimation on the damages due to the massive flood is in the vicinity of RM 1 billion. Therefore, the restoration should be completed adequately with proper planning and management.